2014
DOI: 10.1155/2014/412786
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning in a Rural Medical School: Feasibility and Educational Benefits in Campus and Clinical Settings

Abstract: Students in a new medical school were provided with laptops. This study explored the feasibility and educational benefits of mobile learning for two cohorts of students learning in two settings-university campus (first-year students) and rural clinical placements (second-year students). Evaluation involved questionnaires, focus groups (faculty and students), and document analysis. Descriptive statistics were computed. Focus groups were audio-recorded, transcribed, and analysed thematically. Response rates for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Consistent with relevant studies (e.g. Kukulska-Hulme, 2005;Nestel et al, 2014), the findings in this study have shown that the use of mobile devices reduced students' physical burden of carrying textbooks and enhanced their accessibility to learning materials. Also similar to the findings of Cacace et al (2005), it was found that the "search" function of mobile devices was valued by the nursing students, as it relieved their cognitive load by speeding up their process of performing time-consuming tasks such as searching for terms and retrieving particular content.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with relevant studies (e.g. Kukulska-Hulme, 2005;Nestel et al, 2014), the findings in this study have shown that the use of mobile devices reduced students' physical burden of carrying textbooks and enhanced their accessibility to learning materials. Also similar to the findings of Cacace et al (2005), it was found that the "search" function of mobile devices was valued by the nursing students, as it relieved their cognitive load by speeding up their process of performing time-consuming tasks such as searching for terms and retrieving particular content.…”
Section: Discussionsupporting
confidence: 92%
“…Byrne-Davis et al (2015) noted the concerns of medical students about the use of mobile technology in their learning, such as the availability of Wi-Fi access; potential theft or infection control; the appropriateness/convenience of using the devices in wards in front of the patients; the possibility of damaging or losing the devices; and the cost of buying the relevant apps or gadgets. Nestel et al (2014) also point out that mobile-aided interaction may not be preferred by students in contacting faculty members.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was also noted that there were sufficient facilities and the education system was prepared to implement the usage of mobiles for learning in their curricula. Nestel et al (2014) concur regarding the positive findings where educational benefits were experienced by students, but highlight that challenges of costs and maintenance have to be addressed in order for full implementation to take place. Hence, mobile learning applications in the academic context is viable since majority of students at universities are confident in using mobile tools and have had positive experiences.…”
Section: Literature Reviewmentioning
confidence: 61%